Effect of Calcium Triphosphate Cement on Proximal Humeral Fracture Osteosynthesis: A Finite Element Analysis. (August 2013) - Kennedy, Jim; Feerick, Emer; McGarry, Patrick; FitzPatrick, David; Mullett, Hannan
Purpose: To measure the effect of void-filling calcium triphosphate cement on the loads at the implant-bone interface of a proximal humeral fracture osteosynthesis using a finite element analysis. Methods: Finite element models of a 3-part proximal humeral fracture fixed with a plate with and without calcium triphosphate cement augmentation were generated from a quantitative computed tomography dataset of an intact proximal humerus. Material properties were assigned to bone fragments using published expressions relating Young's modulus to local Hounsfield number. Boundary conditions were then applied to the model to replicate the physiological loads. The effect of void-filling calcium triphosphate cement was analysed. Results: When the void was filled with calcium triphosphate cement, the pressure gradient of the bone surrounding the screws in the medial fracture fragment decreased 97% from up to 21.41 to 0.66 MPa. Peak pressure of the fracture planes decreased 95% from 6.10 to 0.30 MPa and occurred along the medial aspect. The mean stress in the screw locking mechanisms decreased 78% from 71.23 to 15.92 MPa. The angled proximal metaphyseal screw had the highest stress. Conclusion: Augmentation with calcium triphosphate cement improves initial stability and reduces stress on the implant-bone interface.